Rationale for a strategic framework to create a competitive space in the domestic consumer market - Chorna, Marina; Buhrimenko, Roman; Zonwire, Austin (Herald of Economics, 2020)
Introduction. Increased competition in the domestic consumer market requires retailers to find new methods of competition on the base of new market spacescreation. Purpose. Formation of strategic bases for creation of retail enterprises by new non-competitive market space. Methods. Analysis and synthesis, SPACE analysis, graphic construction, scientific abstraction. Results. The author’s vision of the strategic thinking concept as a basis for strategic transformation of an enterprise to new market space, which forms on the base of the needs of strategic self-identification, awareness of strategic risk and strategic protection, is presented. The role of strategic intuition and its essence in decision making is clarified. The comprehensive approach is proposed for determining the degree of market environment compaction and, accordingly, of competition (market lever), in which the existence of an enterprise under traditional competition laws is unlikely. On the base of comparative analysis, the feasibility of applying the principles of the SPACE coordinate system for constructingthe market lever in the following areas: market saturation, influencebranching, intellectual capacity, innovativeness is substantiated. Each direction is interpreted in meaningful criteria which are determined by the relevant indices. All indices of the market lever system are unified and standardized in their architecture, which allows their generalizing into single system and forming integral values in each of the four directions. Discussion. Interpreting the results of the market leverposition assessment, determining the necessary and sufficient boundaries of the market space (the formation of the blue and red oceans), are worth doing as they will determine the enterprise’sstrategic alternatives.